BEAN ROCAMEX 1 2 AND 3 THREE IMPROVED VARIETIES OF BEANS FOR PLANTING WITHOUT IRRIGATION IN THE MESA CENTRAL - WELLHAUSEN, EJ; ROBERTS, LM; MUNOZ, JOSE MAURICIO; LINTON S, CARLOS (Hospital General, CD MEXICO, DF, MEX, 1979)
One phase of the cooperative corn improvement program being carried on by the Mexican Dept of Agriculture and the Rockefeller Foundation has been the collection and testing of native open-pollinated vars In small isolated areas certain vars have been f
PHYS REV B
Keywords: BEAN ROCAMEX 1, 2 AND 3, IMPROVED VARIETIES OF BEANS, PLANTING WITHOUT IRRIGATION, MESA CENTRAL; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL